CREST: clinical bleeding and risk evaluation in hematology–oncology patients: a systematic review and meta-analysis of thromboelastography's role. Issue 7 (12th October 2022) - Khoo, Charis E.H.; Long, Melody H.; Shi, Luming; Guo, Liang; Hee, Hwan Ing
Abstract : Thrombocytopenia and bleeding are common complications of hematologic malignancies. Often, prophylactic platelets are administered to minimize bleeding risk, based on total platelet count (TPC). However, TPC is a poor predictor, and does not provide rapid information. This review presents a novel prospective in the use of point-of-care viscoelastic studies to assess bleeding risk and guide transfusion therapy in a haematological oncological population, where its use can be extended to a ward level as a bedside test. Monitoring TEG maximum amplitude trends may be useful to guide transfusion protocols, especially for patients with total platelet counts ranging 30–100 × 10 9 /l. Fibrinogen assessment in this group of patients may identify other blood components that require replacing to reduce bleeding risk. Normal maximum amplitude parameters for patients with low platelet counts can be a reassuring sign. This meta-analysis serves to remind the reader that absolute platelet quantity does not equate to the quality of clot formation.